Testbeds and research infrastructures for the development of networks and communications : 13th EAI International Conference, TridentCom 2018, Shanghai, China, December 1-3, 2018, Proceedings /: 13th EAI International Conference, TridentCom 2018, Shanghai, China, December 1-3, 2018, Proceedings. (2019) - Unknown
No abstract available